Comparison between the effect of free weight and machine exercise on the quadriceps muscles among male students in IIUM Kuantan - Mohamed Haslan, Aliff Hafizuddin; Mohamad, Mohd Yusof (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2025)
Background: Exercise, particularly resistance training, plays a crucial role in an individual’s overall fitness. This research aimed to compare the efficacy of free-weight (FW) versus machine-based (MB) resistance training towards the changes in quadriceps muscle girth among the male students at the International Islamic University Malaysia (IIUM) Kuantan. Methods: Twenty-four (N=24) male students (age range) were selected and underwent an eight-week resistance training program. Participants were divided into FW (n=12) and MB (n=12) training groups. Participants trained twice weekly, and quadriceps muscle girth were measured using a measuring tape at week four (W4) and eight (W8). Results: Quadriceps size significantly increased with both free weights (52.74±3.22 to 54.43±3.24) and machines (52.66±5.48 to 54.35±5.40) over 4 and 8 weeks (p < 0.001). Conclusion: FW and MB were beneficial for individuals seeking to improve their quadriceps muscle size changes following eight weeks of training